Pelatihan budidaya ikan gurami pada POKDAKAN Enggal Jaya Desa Beji - Setyaningsih, Gustin; Sarmin, Sarmin; Pribadi, Prayoga; Ramadhan, Rifqi Falih; Seno, Axel Sandi; Khumaeni, Eko Hidayaturrohman (Universitas Pahlawan Tuanku Tambusai, 2025)
Beji Village, Kedungbanteng District, is a center for gourami cultivation in Banyumas Regency. During the cultivation process, fish farmers encounter problems regarding proper gourami cultivation practices, resulting in the death of broodstock. Farmers rely solely on traditional knowledge based on field experience, lacking expert guidance. Every year, gourami experience mass mortality, the most severe of which occurred in 2018, with a mortality rate of 90%. Most broodstock deaths are caused by viruses, water quality, weather, and other factors. This has resulted in economic losses for farmers in the Enggal Jaya group, with annual decreases in gourami egg production. Gourami broodstock mortality can be prevented with proper cultivation management. The training aimed to improve farmers' skills in gourami cultivation. The training methods used were lectures and discussions. Based on the participants' evaluation forms, it can be concluded that 72% of the training participants experienced increased knowledge about gourami cultivation.